Exploring the potential for social prescribing in pre‐hospital emergency and urgent care: A qualitative study. (11th March 2021) - Scott, Jason; Fidler, Gayle; Monk, Daniel; Flynn, Darren; Heavey, Emily
Abstract: There is a sustained increase in demand for emergency and urgent care services in England. The NHS Long Term Plan aims to reduce the burden on emergency hospital services through changing how pre‐hospital care operates, including increased delivery of urgent care. Given the recognised potential of social prescribing to address wider determinants of health and reduce costs in other settings, this study aimed to understand the role that social prescribing can play in pre‐hospital emergency and urgent care from the perspectives of staff. Semi‐structured interviews ( n  = 15) and a focus group ( n  = 3) were conducted with clinical staff ( n  = 14) and non‐clinical health advisors ( n  = 4) from an English Ambulance Service covering emergency (999) and non‐emergency (111) calls. Data were analysed using a pre‐defined framework: awareness of social prescribing; potential cohorts suitable for social prescribing; and determinants of social prescribing. Awareness and knowledge of social prescribing was limited, though when social prescribing was explained to participants they almost universally recognised its benefits for their role. Social prescribing was considered to be most beneficial to those calling for reasons relating to mental health, loneliness or social isolation, in particular older people and frequent users of 999 and 111 services. Determinants of social prescribing were identified across the micro (patient and staff acceptability of social prescribing), meso (triage and referral pathways) and macro (commissioning and funding) levels of analysis. This is the first empirical study to explore social prescribing in pre‐hospital emergency and urgent care services, which suggests that it has potential to improve quality of care at the point of people accessing these services. There is a pressing need to address the micro, macro and meso level determinants identified within this study, in order to support staff within pre‐hospital emergency and urgent care services to socially prescribe.